Optimalisasi Pembelajaran Sejarah di Sekolah Dasar Melalui Metode Interaktif dan Kreatif : Tinjauan Pustaka - Refina Maylanda; Adrias Adrias; Salmaini Safitri Syam (Lembag, 2025)
History learning in elementary schools plays an important role in shaping students' understanding of past events and instilling national values. However, the conventional approach that is still widely applied often results in low student interest and participation in history learning. This article aims to analyze various interactive and creative methods in history learning in elementary schools through a literature review. Interactive methods, such as group discussions, role-playing, and the use of digital media, as well as creative methods, such as storytelling, concept maps, and exploration-based projects, have been shown to increase student engagement and deeper understanding of historical concepts. Various studies have shown that the application of these methods not only increases students' learning motivation but also develops critical, analytical, and collaborative thinking skills. In addition, the use of technology such as educational applications and historical simulations further enriches students' learning experiences, making them more contextual and relevant to everyday life. However, the application of this method still faces challenges, such as limited resources, teacher readiness, and support from the school environment. Therefore, an appropriate implementation strategy is needed, including teacher training and the provision of adequate learning facilities. This literature review is expected to provide insight for educators and researchers in developing more effective and interesting history learning methods for elementary school students.